Supercritical CO2 phase transition and permeability variation characteristic under coupling effect of temperature and confining stress - Hongbo YAO; Weiguo LIANG; Jie WEI (Meitan xuebao)
In the process of CO2 sequestration in deep coal seam, the pressure of injected supercritical CO2 gradually decreases with the increase of migration distance, and it turns into gaseous state. This kind of CO2 with phase change in coal is called mixed-phase CO2. The pressure distribution characteristics and permeability of mixed-phase CO2 in coal are important factors affecting the sealing effect. The traditional gas permeability is based on the assumption of linear distribution of gas pressure. However, the physical properties of CO2 in complex phase state are complicated, and the assumption of linear distribution of pore pressure may no longer be applicable. In this paper, the pressure evolution characteristics of mixed-phase CO2 were studied on ø100 mm×200 mm anthracite raw coal sample at different temperatures (40, 55, 70, 85 ℃) and confining pressures (25, 35, 45 MPa). The results showed as follows: ① the mixed-phase CO2 pressure in coal showed a nonlinear decreasing trend of first slow and then sharp. The actual average pore pressure is about 0.6−0.7 times of the injection pressure. ② The difference between the permeability of mixed-phase CO2 calculated based on the modified average pore pressure and that calculated by the traditional Darcy’s law gradually decreases to below 20% with the increase of confining pressure and temperature. ③ Under the comprehensive influence of coal thermal expansion, CO2 desorption and viscosity, the mixed-phase CO2 permeability decreases first and then increases with temperature. ④ When supercritical CO2 is injected, with the decrease of pore pressure, the internal permeability changes in a U shape, and the minimum value appears in the CO2 phase transition zone. The permeability of gaseous CO2 decreases with the increase of pore pressure, while the permeability of supercritical CO2 increases with the increase of pore pressure, which is the result of adsorption expansion and effective stress.